When Words Do Not Work: Exploring Preservice Teachers’ Confidence in Teaching Reading to English Learners - Christina M Pavlak; Monica Cavender (Networks: An Online Journal for Teacher Research, 2019)
This practitioner research study explores what happens when students in a Master of Arts in Teaching (MAT) program are engaged in a clinical experience at an urban pre-K-8th-grade school with a majority English Learner (EL) population. Specifically examined is preservice teachers’ confidence in implementing strategies to meet the needs of ELs in beginning reading. Data sources included: a survey, a written reflection, weekly lessons plans, blog entries, and informal observations of small group instruction and class participation. Qualitative analysis (Charmaz, 2000, 2003, 2005) was used. Results from this study point to the need for teacher preparation programs to support teacher candidates in working with ELs in clinical settings. This research has also informed the authors’ teaching of this clinical course in addition to the design and implementation of a new course aimed at preparing teacher candidates to work with ELs in mainstream classrooms.
Keywords: English learners; literacy; teacher research; teacher education